Peran Teknologi dalam Implementasi Kurikulum Merdeka - Oemi Koelsoem; Kusmiyati Kusmiyati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Curriculum is an essential component of the education system, as the two are closely interconnected. Analogously, the curriculum can be likened to the heart in the human body. When the heart functions well, the entire body system will operate optimally. Similarly, if the curriculum is effectively implemented and supported by well-functioning elements, the learning process will run smoothly, producing high-quality learners. The purpose of this study is to evaluate how educational technology contributes to the implementation of the Merdeka Curriculum. This qualitative research uses a literature study, also known as a Systematic Literature Review (SLR), aimed at comparing current theories with those discussed in previous research literature. The literature sources referenced come from research findings and studies published in scientific articles, accessed through electronic literature search engines such as Mendeley and Google Scholar. The results of this study show that educational technology plays a crucial role in supporting the Merdeka Curriculum, as well as having a positive impact on the implementation of the Merdeka Belajar concept in practice. The continuously evolving Merdeka Curriculum helps facilitate the integration of the latest information technology for students.